2015
DOI: 10.1016/j.bjid.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The burden of sepsis in critically ill human immunodeficiency virus-infected patients—a brief review

Abstract: Since the advent of highly active antiretroviral therapy in 1996, we have seen dramatic changes in morbi-mortality rates from human immunodeficiency virus-positive patients. If on the one hand, the immunologic preservation-associated with the use of current antiretroviral therapy markedly diminishes the incidence of opportunistic infections, on the other hand it extended life expectancy of human immunodeficiency virus-infected individuals similarly to the general population. However, the management of critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have shown that irrespective of the use of HAART, sepsis among HIV-infected patients is increasing, while the incidence of acute respiratory insufficiency and Pneumocystisrelated pneumonia is decreasing. [7][8][9] In HIV-infected patients, sepsis accounted for 12 -31% of HIV-positive patients' admission to intensive care units (ICUs), and was associated with a worse prognosis. [7][8][9][10] Despite the significant prevalence of the disease in KZN, the impact of HIV co-infection on the clinical outcome of surgical patients in our setting remains largely unknown.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that irrespective of the use of HAART, sepsis among HIV-infected patients is increasing, while the incidence of acute respiratory insufficiency and Pneumocystisrelated pneumonia is decreasing. [7][8][9] In HIV-infected patients, sepsis accounted for 12 -31% of HIV-positive patients' admission to intensive care units (ICUs), and was associated with a worse prognosis. [7][8][9][10] Despite the significant prevalence of the disease in KZN, the impact of HIV co-infection on the clinical outcome of surgical patients in our setting remains largely unknown.…”
Section: Researchmentioning
confidence: 99%
“…[7][8][9] In HIV-infected patients, sepsis accounted for 12 -31% of HIV-positive patients' admission to intensive care units (ICUs), and was associated with a worse prognosis. [7][8][9][10] Despite the significant prevalence of the disease in KZN, the impact of HIV co-infection on the clinical outcome of surgical patients in our setting remains largely unknown. Over a decade ago, and prior to the national roll-out of the HAART programme, a study by Cacala et al [2] showed that HIV status does not influence the clinical outcome in general surgical patients.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…PLHIV with sepsis have a poorer prognosis due to delay in diagnosis and prompt treatment, and altered pattern of immune response due to immune dysregulation associated with chronic HIV infection. [1214]…”
Section: Discussionmentioning
confidence: 99%
“…This data is lower compared to the findings in this study (89.5%). Furthermore, sepsis is related to increased length of stay in the ICU (26) . This, in turn, was also a variable with statistical significance in the outcome of ICU admission, which reflects its impact on the health condition of HIV-positive patients.…”
Section: Introductionmentioning
confidence: 99%